Water, To Do What and for Whom? Discourse on Use and Distribution of Water in Chile and its Impacts on Agricultural Production - Sagredo Aylwin, María Paz (2025)
The article analyzes how the discourses and demands of actors involved in agricultural activities in the Coquimbo Region (Chile), among the peasant organizations, trade associations of medium-sized and large producers and public organizations, reflect different views and tensions regarding water scarcity product of the decrease in precipitations and the system of access and distribution of water for irrigation. Using elements of political ecology and discourse analysis, we seek to understand how actors elaborate their discourses on water scarcity and how they adapt other discourses on the topic based on their own interests. The article concludes that, although there are common elements and concepts in all discourses, these reflect different demands and tensions among local producers, and between them and public services. In the case of peasant organizations, water scarcity is addressed as a threat to a rural way of life, from the business sphere it is conceived as a threat to food production and exportation, and for public organizations it is addressed as a risk to environmental sustainability and food security and sovereignty.